A 3-Year Retrospective Study of the Epidemiology of Acute Respiratory Viral Infections in Pediatric Patients With Cancer Undergoing Chemotherapy. Issue 4 (May 2019) - Aydin Köker, Sultan; Demirağ, Bengü; Tahta, Neryal; Bayram, Nuri; Oymak, Yeşim; Karapinar, Tuba H.; Gözmen, Salih; Düzgöl, Mine; Erçan Bozyer, Hazer; Vergin, Canan; Devrim, İlker
Abstract : Background: Acute viral respiratory infections are common causes of febrile episodes in children. There are still limited data about distribution of acute viral respiratory infections in children with cancer. Objective: The first aim of this study was to evaluate the viral etiology and seasonality of acute viral respiratory infection in pediatric patients with cancer in a 3-year study. Our second aim was to evaluate the impact of viral infections on delaying the patients' chemotherapy or radiotherapy. Materials and Methods: This cross-sectional study was conducted from January 2014 to July 2017. Nasopharyngeal aspirates were analyzed in patients younger than 21 years with acute respiratory infections. Patients were treated in the Pediatric Hematology and Oncology Department of Dr. Behçet Uz Children's Hospital with real-time multiplex polymerase chain reaction. Data were analyzed to determine the frequency and seasonality of infections. The χ 2 or the Fisher exact tests were used. Results: A total of 219 samples of nasopharyngeal aspirates and blood were analyzed. The mean patient age was 76.8±59.3 months, with 46.3% female and 53.7% male children in a total of 108 patients. Of this total, 55% (60/108 cases) had multiple acute respiratory infections. Acute lymphoblastic leukemia (48.1%) was the most prevalent disease. The 3 most prevalent viruses were human rhinovirus (HRV) (33.1%), parainfluenza (PI) (18.7%), and coronavirus (CoV) (14.8%). In terms of the seasonal distribution of viruses, PI was most common in winter 2014, HRV in spring 2014, HRV in fall 2014, PI in winter 2015 and summer 2015, CoV in spring 2015, HRV in fall 2015, both influenza and HRV in winter 2016, both human metapneumovirus and bocavirus in spring 2016, HRV in summer 2016, both HRV and PI in fall 2016, both respiratory syncytial virus and influenza in winter 2017, HRV in spring 2017, and both HRV and adenovirus in summer 2017. The mean duration of neutropenia for patients with viral respiratory infection was 17.1±13.8 (range: 2 to 90) days. The mean duration of symptoms of viral respiratory infection was 6.8±4.2 (range: 2 to 31) days. A delay in chemotherapy treatment owing to viral respiratory infection was detected in 73 (33.3%) patients. The mean duration of delay in chemotherapy treatment was 9.6±5.4 (range: 3 to 31) days. Conclusions: In conclusion, we report our 3-year experience about the frequency and seasonality of respiratory viruses in children with cancer.